Exam ref MS-101 Microsoft 365 Mobility and Security - Svidergol, Brian; Clements, Bob (Microsoft : Pearson Education, 2019)
Prepare for Microsoft Exam MS-101 and help demonstrate your real-world mastery of skills and knowledge needed to manage Microsoft 365 mobility, security, and related administration tasks. Designed for experienced IT professionals, Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Expert level. Focus on the expertise measured by these objectives: Implement modern device services Implement Microsoft 365 security and threat management Manage Microsoft 365 governance and compliance This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you are a Microsoft 365 Enterprise Administrator who participates in evaluating, planning, migrating, deploying, and managing Microsoft 365 services About the Exam Exam MS-101 focuses on knowledge needed to implement Mobile Device Management (MDM); manage device compliance; plan for devices and apps; plan Windows 10 deployment; implement Cloud App Security (CAS), threat management, and Windows Defender Advanced Threat Protection (ATP); manage security reports and alerts; configure Data Loss Prevention (DLP); implement Azure Information Protection (AIP); and manage data governance, auditing, and eDiscovery. About Microsoft Certification Passing this exam and Exam MS-100 Microsoft 365 Identity and Services (and earning one Microsoft 365 workload administrator certification or the MCSE: Productivity certification) fulfills your requirements for the Microsoft 365 Certified: Enterprise Administrator Expert certification credential. This demonstrates your ability to evaluate, plan, migrate, deploy, and manage Microsoft 365 services. See full details at: microsoft.com/learn.